uman observations of the placenta in Puno 3,812 m. height - Passano Passano, Sebastián (2015)
The author has studied 2,684 deliveries occurred in Puno (Perú) at 3,812 m. of altitude; he divided the total in 2 groups: 1) 2,502 women living permanently above 3,000 m. of altitude. 2) 182 women living at places lower than 2,800 m. that during pregnancy went to live at Puno (3,000 m.) where they were delivered. In both groups he found a positive correlation between weight of placenta and weight of the fetus, however in group (1) 60% of the placentas had weight, diameter and central thickness above the normal sea level standards. In group (2) there were 23% of newborn with a weight lower than 2,500 gr., compared with only 8.2 % in group (1).